2021
DOI: 10.3390/ijerph18168756
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Tecar Therapy on Skin Temperature, Ankle Mobility and Hyperalgesia in Myofascial Pain Syndrome in Professional Basketball Players: A Pilot Study

Abstract: (1) Background: Myofascial pain syndrome (MPS) is a clinical condition characterized by localized non-inflammatory musculoskeletal pain caused by myofascial trigger points. Diathermy or Tecar therapy (TT) is a form of noninvasive electro-thermal therapy classified as deep thermotherapy based on the application of electric currents. This technique is characterized by immediate effects, and its being used by high performance athletes. (2) Methods: A total of thirty-two participants were included in the study who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…These are just a few examples of investigations that raise questions about the relevance of using stretching or foam rolling, specifically, when aiming to acutely improve ROM. As we found, several other interventions achieved the same goal, including cycling 26 , 88 and hot water baths, 29 , 88 eccentric stiff-leg deadlifts, 89 , 90 whole body vibration, 91 cryotherapy, 92 , 93 different massage techniques, 94 electromyostimulation, 95 , 96 and Tecar therapy, 97 as well as yoga (alone 98 or combined with heat 99 ). In some studies, effects of alternative interventions provided greater ROM than those induced by stretching or foam rolling.…”
Section: Discussionsupporting
confidence: 57%
“…These are just a few examples of investigations that raise questions about the relevance of using stretching or foam rolling, specifically, when aiming to acutely improve ROM. As we found, several other interventions achieved the same goal, including cycling 26 , 88 and hot water baths, 29 , 88 eccentric stiff-leg deadlifts, 89 , 90 whole body vibration, 91 cryotherapy, 92 , 93 different massage techniques, 94 electromyostimulation, 95 , 96 and Tecar therapy, 97 as well as yoga (alone 98 or combined with heat 99 ). In some studies, effects of alternative interventions provided greater ROM than those induced by stretching or foam rolling.…”
Section: Discussionsupporting
confidence: 57%
“…All of these effects significantly reduce muscle and/or joint pain, improving the function of these tissues [9,13,16,20,[25][26][27][28][29]. However, the Yeste-Fabregat [30] study showed that there was hypersensitivity in trigger points immediately after the application of Tecar. When compared to other physiotherapy techniques, there was a 10% reduction in pain after 30 minutes of application.…”
Section: Discussionmentioning
confidence: 99%
“… 13 In contrast, the amino acid sequence of GAP-43 lacks membrane-spanning domains and glycosylation sites. 14 , 15 GAP-43 is highly hydrophilic; however, it contains a short (43 amino acids) hydrophobic fragment that facilitates the anchoring of this neurotrophic factor to the cytoplasmic side of synaptic plasma membranes. 16 The overriding process affecting the formation of the biologically active form of GAP-43 is phosphorylation.…”
Section: Introductionmentioning
confidence: 99%